Distinct fecal microbial signatures are linked to sex and chronic immune activation in pediatric HIV infection - Rosel-Pech, Cecilia; Pinto-Cardoso, Sandra; Chávez-Torres, Monserrat; Montufar, Nadia; Osuna-Padilla, Iván; Ávila-Ríos, Santiago; Reyes-Terán, Gustavo; Aguirre-Alvarado, Charmina; Matías Juan, Norma Angelica; Pérez-Lorenzana, Héctor; Vázquez-Rosales, José Guillermo; Bekker-Méndez, Vilma Carolina (Frontiers in Immunology, 2023)
Introduction: Our understanding of HIV-associated gut microbial dysbiosis in children perinatallyinfected with HIV (CLWH) lags behind that of adults living with HIV. Childhood represents a critical window for the gut microbiota. Any disturbances, including prolonged exposure to HIV, antiretroviral drugs, and antibiotics are likely to have a significant impact on long-term health, resulting in a less resilient gut microbiome. The objective of our study was to characterize the gut microbiota in CLWH, and compare it with HIV-unexposed and -uninfected children.We enrolled 31 children aged 3 to 15 years; 15 were CLWH and 16 were HUU. We assessed dietary patterns and quality; quantified soluble and cellular markers of HIV disease progression by flow cytometry, enzyme-linked immunosorbent and multiplex-bead assays, and profiled the gut microbiota by 16S rRNA sequencing. We explored relationships between the gut microbiota, antibiotic exposure, dietary habits, soluble and cellular markers and host metadata.Results: Children had a Western-type diet, their median health eating index score was 67.06 (interquartile range 58.76-74.66). We found no discernable impact of HIV on the gut microbiota. Alpha diversity metrics did not differ between CLWH and HUU. Sex impacted the gut microbiota (R-squared= 0.052, PERMANOVA p=0.024). Male children had higher microbial richness compared with female children. Two taxa were found to discriminate female from male children independently from HIV status: Firmicutes for males, and Bacteroides for females. Markers of HIV disease progression were comparable between CLWH and HUU, except for the frequency of exhausted CD4+ T cells (PD-1+) which was increased in CLWH (p=0.0024 after adjusting for confounders). Both the frequency of exhausted CD4+ and activated CD4+ T cells (CD38+ HLADR+) correlated positively with the relative abundance of Proteobacteria (rho=0.568. false discovery rate (FDR)-adjusted p= 0.029, and rho=0.62, FDR-adjusted p=0.0126, respectively).The gut microbiota of CLWH appears similar to that of HUU, and most markers of HIV disease progression are normalized with long-term ART, suggesting a beneficial effect of the latter on the gut microbial ecology. The relationship between exhausted and activated CD4+ T cells and Proteobacteria suggests a connection between the gut microbiome, and premature aging in CLWH.